2020
DOI: 10.30684/etj.v38i4a.263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Octane Number on Performance and Exhaust Emissions of an SI Engine

Abstract: Spark ignition engines are very popular engines that they are running millions of vehicles all over the world. This engine emits many harmful pollutants, such as CO, UHC, and NOX. In this paper, the impact of gasoline octane number on the engine performance and exhaust emissions was studied. In the tests, four-cylinder, four-stroke engine, and two variable octane numbers (RON83 and 94.5) were used. The engine was run at different engine speeds and loads. The results from the experimental study indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…This study shows that peak torque and peak power are highest produced by 90-octane fuel. Further recent research [19] regarding the effect of octane number on performance and exhaust emissions in 150cc Honda engines using 90, 92 and 98 octane fuel. This study concluded that 90 octane produces torque and effective power stably compared to other octane fuels.…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that peak torque and peak power are highest produced by 90-octane fuel. Further recent research [19] regarding the effect of octane number on performance and exhaust emissions in 150cc Honda engines using 90, 92 and 98 octane fuel. This study concluded that 90 octane produces torque and effective power stably compared to other octane fuels.…”
Section: Introductionmentioning
confidence: 99%